Fractal Image Compression Method for Lossy Data Compression - Artuger, Firat; Ozkaynak, Fatih (Ieee, 2018)
One of the most commonly used methods for lossy image compression today is the JPEG compression method. However, the JPEG compression method has its disadvantages. To overcome these disadvantages, a fractal image compression method is proposed. JPEG compression gives good results on small-sized images, but it suffers from large-sized images, and as the size of the image increases, both accuracy and compression ratio decrease and compression and decoding take a long time. However, the fractal compression method removes these troubles. The programs are written in matlab and the results are evaluated. As the size of the images increases, it is observed that the fractal compression method is more suitable.
Kayipli Veri Sikistirma için Fraktal Görüntü Sikistirma Yöntemi
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: Image Compression; JPEG Compression Method; Fractal Image Compression Method; Lossy Data Compression